Pengaruh Pendidikan Kesehatan Pertolongan Pertama Luka Bakar Terhadap Pengetahuan Ibu Rumah Tangga di Desa Sea Kab. Minahasa - Arbie Chandra Abas; Tezar Nusi; Rahmat Hidayat Djalil; Sunarti Basso (Jurnal Kesehatan Amanah, 2024)
Burns are one of the types of injuries that often occur in everyday life, whether at home, workplace, or around us. Burns in housewives often occur due to daily activities at home. The purpose of the study is to determine the influence of first aid education burns on housewives’ knowledge in Sea Village, Minahasa Regency. The research was conducted using pre-experimental methods with one group prepest-posttest design. The sample totaled 21 respondents taken using purposive sampling. Data collection is done using questionnaires. Further data collected in analysis with McNemar statistical test with a level of meaning (α) 0.05. The results of the study were obtained in the influence of first aid education burns on housewives’ knowledge with value P = 0.000 which means that the value is smaller than P(α)=0.05. The conclusion in this study is that there is the influence of first aid education on burns knowledge of housewives. Therefore, it is expected that this intervention can be useful and practical information in daily life.